IMPROVING THE STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXT BY USING FABLE AT EIGHT GRADE OF MTS AL – MANAAR PTPN I PULU RAJA - ALFI HIDAYANI, NURUL (BRIGHT VISION Journal of Language and Education, 2022)
The research was aimed to improve the students’ reading comprehension on narrative text by using fable. The subject of this study was the eighth grade students of MTs Al – Manaar PTPN IV Pulu Raja in 2020/2021 academic year. It was consisted of one class and 27 students as respondents. The object of this research was to improve the students’ reading comprehension on narrative text by using fable. This research of this study was conducted by using classroom action research. The technique of analyzing the data was qualitative and quantitative research. The qualitative data were taken from observation. While the quantitative data were taken from tests consist of pre – test and post – test. Based on the result of the data analysis, it shows that there was an improvement in the students’ reading comprehension on narrative text after using fable. In pre – test the students mean was 33, 51 or it was 0%. All of the students did not reach the KKM. After doing the post – test, there was an improvement in the result of the students’ mean. The students’ mean in post – test cycle 1 was 55, 74 or it was 22.22%, and the students’ mean in the post – test cycle 2 was 80, 74 or it was 85, 18%. In other words the students’ reading comprehension on narrative text was improved. And based on the observation sheet and documentation, it was showed that the expression and excitement of the students were also improved.